Søren Kierkegaard - Hannay, Alastair (Critical lives, 2018)
The Danish philosopher and religious author Søren Kierkegaard (1813-1855) is widely considered to be one of the most important thinkers of the modern age. He is known as the 'father of existentialism,' but his work was also influential on theories of modernism, theology, Western culture, Church politics and the Christian faith. His wit, imagination and humour have inspired a generation of followers from Franz Kafka to Woody Allen. Yet how did this inattentive schoolboy rise to critique the work of great thinkers such as Hegel and the German Romantics? Who was the unusual person writing behind the many pseudonyms? And in what way are Kierkegaard's concepts relevant today? In this absorbing new biography, Alastair Hannay unravels the mystery of Søren Kierkegaard's short but momentous career. Kierkegaard's key concepts and major works are described alongside the major incidents in his private and public life, from his longing for selfhood expressed at the age of 22, to a verbal assault on the Church in the months prior to his early death at the age of 42. Søren Kierkegaard is the story of a man destined from youth to become a thorn in the side of society--back cover